Applications of remote epitaxy and van der Waals epitaxy - Ilpyo Roh; Seok Hyeon Goh; Yuan Meng; Justin S. Kim; Sangmoon Han; Zhihao Xu; Han Eol Lee; Yeongin Kim; Sang-Hoon Bae (Nano Convergence, 2023)
Abstract Epitaxy technology produces high-quality material building blocks that underpin various fields of applications. However, fundamental limitations exist for conventional epitaxy, such as the lattice matching constraints that have greatly narrowed down the choices of available epitaxial material combinations. Recent emerging epitaxy techniques such as remote and van der Waals epitaxy have shown exciting perspectives to overcome these limitations and provide freestanding nanomembranes for massive novel applications. Here, we review the mechanism and fundamentals for van der Waals and remote epitaxy to produce freestanding nanomembranes. Key benefits that are exclusive to these two growth strategies are comprehensively summarized. A number of original applications have also been discussed, highlighting the advantages of these freestanding films-based designs. Finally, we discuss the current limitations with possible solutions and potential future directions towards nanomembranes-based advanced heterogeneous integration. Graphical Abstract